"Everything was fine"*: An analysis of the drill crew's situation awareness on Deepwater Horizon. (November 2015) - Roberts, R.; Flin, R.; Cleland, J.
Abstract: Purpose: Investigation reports into the Deepwater Horizon drilling rig disaster identified issues with the drill crew's situation awareness (SA). The aim was to (1) apply the Driller's Situation Awareness (DSA) model to the cognitive data extracted from accident reports from this event to determine if it could help to explain why the crew erroneously concluded that the well was stable, which would (2) provide a preliminary evaluation of the model's validity. Method: The DSA model was used for a content analysis of the SA components in the accounts of the crew's actions during two Negative Pressure Tests (NPT), in the hours before the blowout. Results: The analysis provided (1) insight into the crew's likely cognitive processes before the blowout. In particular, it revealed issues with their interpretation and mental models of the well state, as well as possible influencing factors including expectation, distraction and experience, emphasising the impact that SA can have on process safety. The categorisation has (2) initially suggested that the DSA model does contain the appropriate components. Limitations: There are limited first hand reports of this event and thus cognitive processes have to be inferred with a degree of caution. Practical implications: The findings give a preliminary validation of the DSA model for further use in training and in investigation of well control events. Recommendations based on the findings are offered for assisting driller SA and consequently, for supporting safe and efficient drilling operations. There is also the opportunity to adapt the DSA model and apply the recommendations from the analysis to similar monitoring positions, where SA is essential, within the process industries. Highlights: The DSA model was applied to a phase of the Deepwater Horizon blowout and preliminarily validated for the drilling domain. The analysis gives insight into why the crew wrongly believed the NPT was successful, showing how inaccurate SA affects safety. Individual and environmental factors were identified that may have impacted on the crew's understanding of the situation. The analysis provides opportunities to learn from the disaster informing recommendations for supporting driller SA.